Instructive role of M‐CSF on commitment of bipotent myeloid cells involves ERK‐dependent positive and negative signaling. Issue 2 (2nd September 2015) - Carras, Sylvain; Valayer, Alexandre; Moratal, Claudine; Weiss‐Gayet, Michèle; Pages, Gilles; Morlé, Francois; Mouchiroud, Guy; Gobert, Stéphanie
Abstract : The role of PKCδ and ERK during molecular mechanism of myeloid differentiation in bipotent progenitors. Abstract : M‐CSF and G‐CSF are instructive cytokines that specifically induce differentiation of bipotent myeloid progenitors into macrophages and granulocytes, respectively. Through morphology and colony assay studies, flow cytometry analysis of specific markers, and expression of myeloid transcription factors, we show here that the Eger/Fms cell line is composed of cells whose differentiation fate is instructed by M‐CSF and G‐CSF, thus representing a good in vitro model of myeloid bipotent progenitors. Consistent with the essential role of ERK1/2 during macrophage differentiation and defects of macrophagic differentiation in native ERK1 −/− progenitors, ERK signaling is strongly activated in Eger/Fms cells upon M‐CSF‐induced macrophagic differentiation but only to a very small extent during G‐CSF‐induced granulocytic differentiation. Previous in vivo studies indicated a key role of Fli‐1 in myeloid differentiation and demonstrated its weak expression during macrophagic differentiation with a strong expression during granulocytic differentiation. Here, we demonstrated that this effect could be mediated by a differential regulation of protein kinase Cδ (PKCd) on Fli‐1 expression in response to M‐CSF and G‐CSF. With the use of knockdown of PKCd by small interfering RNA, we demonstrated that M‐CSF activates PKCd, which in turn, inhibits Fli‐1 expression and granulocytic differentiation. Finally, we studied the connection between ERK and PKCd and showed that in the presence of the MEK inhibitor U0126, PKCd expression is decreased, and Fli‐1 expression is increased in response to M‐CSF. Altogether, we demonstrated that in bipotent myeloid cells, M‐CSF promotes macrophagic over granulocytic differentiation by inducing ERK activation but also PKCd expression, which in turn, down‐regulates Fli‐1 expression and prevents granulocytic differentiation.